2022
DOI: 10.3389/fnins.2022.801618
|View full text |Cite
|
Sign up to set email alerts
|

Automated Segmentation of Midbrain Structures in High-Resolution Susceptibility Maps Based on Convolutional Neural Network and Transfer Learning

Abstract: BackgroundAccurate delineation of the midbrain nuclei, the red nucleus (RN), substantia nigra (SN) and subthalamic nucleus (STN), is important in neuroimaging studies of neurodegenerative and other diseases. This study aims to segment midbrain structures in high-resolution susceptibility maps using a method based on a convolutional neural network (CNN).MethodsThe susceptibility maps of 75 subjects were acquired with a voxel size of 0.83 × 0.83 × 0.80 mm3 on a 3T MRI system to distinguish the RN, SN, and STN. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…15-20, 51, 52 Among these, some are based on QSM data. [15][16][17][18]20 Our results are in line with those of the best performing approaches which reach around 90% of Dice accuracy. 15,17,18 However, these three studies only included healthy controls.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…15-20, 51, 52 Among these, some are based on QSM data. [15][16][17][18]20 Our results are in line with those of the best performing approaches which reach around 90% of Dice accuracy. 15,17,18 However, these three studies only included healthy controls.…”
Section: Discussionsupporting
confidence: 87%
“…[15][16][17][18]20 Our results are in line with those of the best performing approaches which reach around 90% of Dice accuracy. 15,17,18 However, these three studies only included healthy controls. Thus, it is unclear how they would perform on patients.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although this distortion is more pronounced in cortical regions, Lau et al 10 found that the geometric distortion between 3T and 7T MRI is on the order of 1 to 2 mm around the subthalamic nucleus, rendering it more difficult to directly use 7T image registration given the lack of contrast in the 3T image to correct for these local distortions. Zhao et al 11 combined the two approaches and applied U-Nets to directly segmenting the STN on high-resolution susceptibility maps and achieved an accuracy on the order of 78% Dice, although they only used healthy subjects.…”
mentioning
confidence: 99%